GREEN BONDS IN INDONESIA: SYNERGY BETWEEN BANK INDONESIA AND OTORITAS JASA KEUANGAN’S COMMITMENT - orima davey; Ria Wierma Putri; Tristiyanto; Yunita Maya Putri; Febryani Sabatira (Journal of Central Banking Law and Institutions, 2023)
Climate change's impact on environmental quality has always been an interesting topic on the international platform, especially for developing countries. As a form of prevention and preparation, the World Bank green bonds by the World Bank have supported developing countries in participating in resilience to climate change. This article uses normative legal analysis with secondary data resources from books and other relevant scientific publications. The study result shows that the World Bank provided numerous recommendations and guidance for developing countries in implementing green bonds in their national regulations. Indonesia is one of the countries that applied green bonds through Bank Indonesia and Otoritas Jasa Keuangan (OJK). Bank Indonesia and OJK are now focusing on developing a Sustainable Finance Instrument (SFI) to stimulate the growth of a green and sustainable economy. A collaboration between the government and the authorities is essential to continuously build and preserve SFI in the market in the long term.